(untitled) (Al-Academy, 2016)
The study of the laptop computer table is one of the important studies at the present time due to the importance of electronic computers that are used in work sites and homes for very long hours, so one of the most important basics of caring for the comfort of the user lies in the design of the laptop table in different shapes and sizes and multiple functions in addition to calculating the measurements of the human body and the extent Its compatibility with the design and measurements of laptop computer tables by taking into account the calculations and measurements of the dimensions of the user’s body of all ages and their consistency and use with the general measurements of the tables and the importance of research comes through the establishment of a knowledge base covering the topic of research to be of benefit to designers and specialists in this field and of benefit to product users as this study is It included all aspects of the tables, and the aim of this study was: to find foundations for building the formal system for the laptop table to be more suitable for the user. As for the limits of the research, the study of the formal system for the laptop table of the Chinese company Havic and available in the Iraqi market during the year 2011-2012 This study contains four chapters, the first chapter includes the research problem and the need for it in addition to oh The amount of research and its objectives and limits. As for the second chapter, it included the previous studies and the theoretical framework, which in turn contained three topics, the first was titled Foundations of Building the Formal System for the Laptop Desk and it contained an overview of the laptop computer, the laptop table, the system, the shape, and the second topic was titled Multifunctionality of the Laptop Table The third topic is on the mechanism of the human body ergonomics and its relationship to the laptop table. And then this chapter ended with indicators. The third chapter includes research procedures and methodology, and includes description and analysis of sample samples according to the axes analysis form. Finally, the fourth chapter included the results of the analysis, conclusions, recommendations and proposals. 1. The design system was distinguished by the efficiency of the functional performance and it helped in that the flat and supportive surface of the table surface in addition to the mechanism of the movement of the legs up and down as well as laterally and this achieved a distinct performance aspect although there were no fans for cooling The laptop computer while working and this was achieved in Form No. (1) and the percentage was 50%, while Model No. (2) achieved higher efficiency in functionality due to the presence of fans and the percentage was 50% .2 The dimensions of the computer tables differed according to the user’s need, as they were voluntary To the user as he wants through the size of the table tops and its inclination mechanism in addition to controlling the height and drop of the table legs. 3 The interconnectedness between the design parts aims to influence the functionality in a good way and this was achieved through the use of appropriate fastening means for the mechanism of movement and movement of the table by 50%